Mindfulness as an Antidote to Burnout for Nursing and Support Staff in an Oncological Intensive Care Unit: A Pilot Study. Issue 5 (September 2022) - Urso, Catherine; Laserna, Andres; Feng, Lei; Agnite, Ashley; Jawe, Neetha; Magoun, Courtney; Layton, Lorraine S.; Nates, Joseph L.; Gutierrez, Cristina
Abstract : We set out to implement a pilot mindfulness-based intervention (MBI) to alleviate burnout, stress, anxiety, and depression in nursing and support staff of an oncological intensive care unit. We created an 8-week personalized yoga therapy MBI for nurses and patient care technicians in an oncological intensive care unit. Validated self-report scale tools were used to measure burnout, stress, anxiety, and depression in the intervention and control groups (Institutional Quality Improvement Registry no. 296, 2018). Changes in scores from baseline to postintervention were evaluated between groups. Forty-five staff, 21 in the control group and 24 in the intervention group, participated. Both groups at baseline had low prevalence of stress, anxiety, and depression (13% vs 36.8%, P = .11; 21.7% vs 52.6%, P = .17; 17.4% vs 26.3%, P = .48; respectively). Low rates of high emotional exhaustion, depersonalization, and low professional efficacy were observed for both groups (41.7% vs 35.0%, P = .65; 20.8% vs 15%, P = .71; 58.3% vs 50.0%, P = .58, respectively). Post-MBI, prevalence of depression, anxiety, stress, emotional exhaustion, and depersonalization remained low and similar between both groups. Notwithstanding, professional efficacy scores significantly improved in a between-group comparison (0.063 vs −0.25; P = .0336). We observed that burnout, stress, anxiety, and depression were remarkably low in our study relative to the literature. Implementation of the MBI faced many obstacles and had low compliance during participation. This presumably influenced results and should be addressed prior to any future intervention. Despite this, professional efficacy improved significantly. Trial registration: Approved by MD Anderson Cancer Center Quality Improvement Registry (no. 296, 2018).